PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Lutfiah Lintang; Sihotang, Veny Rahmayani; Riznanda, Annisa; Dwi, Mizta; Furqoni , Hafizah (Educandumedia: Jurnal Ilmu pendidikan dan kependidikan, 2022)
This development research aims to produce problem-based learning-based student worksheet (LKPD) products that can improve students' mathematical problem-solving abilities that are valid. This study uses the development of a 4-D Research and Development (R&D) model which includes four stages, namely define, design, develop, and disseminate. However, it is modified so that this research is only up to 3-D which includes three stages, namely the stages of defining (define), design (design), and development (develop). The results of the research resulted in the development of valid problem-based learning-based student worksheets to improve mathematical problem solving for junior high school students. Based on the results of the student worksheet validator assessment questionnaire, the value of the media expert was 4.0 with valid criteria, the material expert was 3.94 with valid criteria and the teacher was 4.25 with very valid criteria, and the Learning Implementation Plan was obtained at 4,16 with valid criteria.